Analysis of Retinal Nerve Fibre Thickening in Progressive and Non-progressive Non-arteritic Anterior Ischaemic Optic Neuropathy Using Optical Coherence Tomography. (2nd September 2020) - Hashimoto, Hirooki; Hata, Masayuki; Kashii, Satoshi; Oishi, Akio; Suda, Kenji; Nakano, Eri; Miyata, Manabu; Tsujikawa, Akitaka
ABSTRACT: The study aims to investigate the longitudinal changes in the circumpapillary retinal nerve fibre layer thickness (cpRNFLT) in progressive and non-progressive non-arteritic anterior ischaemic optic neuropathy (NAION). This retrospective observational case series study analysed 17 eyes with NAION. Patients sustaining any additional visual loss (additional decrease in visual acuity (VA) ≥0.2 logMAR) within two months after initial onset of symptoms were classified as having progressive NAION. Of the 17 eyes with NAION, 13 (76.5%) were diagnosed as non-progressive and 4 (23.5%) were diagnosed as progressive. Compared with control eyes, eyes with non-progressive NAION showed greater cpRNFLT in all four optic disc quadrants at the initial visit (temporal and superior: P < .001; nasal and inferior: P = .002). In contrast, compared with control eyes, eyes with progressive NAION showed greater cpRNFLT in the superior and nasal quadrants ( P = .004 and 0.028, respectively), but not in the temporal and inferior quadrants. During progression, eyes with progressive NAION showed a significant increase in cpRNFLT in the inferior quadrants; furthermore, there was significant increase in cpRNFLT in the nasal sector before visual loss developed after the initial visit. Progressive NAION showed development of the disc swelling from the superior to inferior portion of optic disc via the nasal swelling, suggesting that swollen axons in one ischaemic part may lead to secondary vascular infarction in another part of the optic disc. This enlargement could constitute the earliest sign of progressive NAION.